Development of an Android-Based Multimedia Learning Application for Human Body Organs to Enhance Middle School Education - Ida Ketut Dedi Jayanta; Bayu Setiaji; Ali Mustopa (Universitas Islam Al-Azhar Mataram, 2024)
In the traditional learning methods where teachers relied on teaching aids like books, some students still struggled to understand the material being taught. This was particularly evident in lessons about human body organs. To create a learning process that is effective, efficient, and aligned with the advancements of modern technology, traditional methods alone are no longer sufficient. A more interactive and engaging learning model is crucial to foster enjoyable and accessible learning experiences. To address this, an Android-Based Multimedia Application for learning about human body organs was developed. This application aims to facilitate the teaching and learning process, especially for middle school students. Through the app, students can access various learning materials such as the respiratory system, digestive system, musculoskeletal system, excretory system, and circulatory system, complemented by images and animations. Additionally, the app includes practice exercises that help students assess their understanding of the material. By leveraging technology, particularly Android and multimedia, the learning process becomes more enjoyable and engaging. The combination of animations, sound, and text enhances the overall learning experience. Students can now access educational materials anytime and anywhere using their Android devices.